DEMOGRAPHY-BASED DEVELOPMENT: THE CHALLENGES OF CIVIL REGISTRATION TO REDUCE POVERTY IN INDONESIA - Kharisma, Dona Budi; Yulianti, Sri Wahyuningsih (Yustisia, 2018)
The present study seeks to analyze the functions of civil registration in poverty reduction and to identify various problems encountered in civil registration in Indonesia. This study was conducted by using an empirical law research. Primary data and legal materials are analyzed qualitatively with empirical juridical approach. The results conclude that civil registration yields demographic data that play a strategic role in the utilization of public services and development planning. Improving the quality of human life, either in the field of education, health or revenue requires demographic data as the policy focus. This gives implications that the basis of development program interventions in the three sectors refer to the aforementioned demographic data. Therefore, the use of demographic data and expansion of the coverage of ownership of demographic documents present as strategic steps for poverty reduction. However, the low attainment of document ownership in some regions and the limited number of civil registration apparatuses become an indicator of the absence of roles of demographic data in development. This has an impact on improperly targeted development planning. Several strategies that need to be implemented include: (1) Strengthening regulations at the regional level that regulate the utilization of demographic data in development planning; (2) establishing study program of civil registration law as an attempt of population-based development in Indonesia.